All-Optical Generation Of Multiwavelength Brillouinerbium Fiber Laser In Long-Wavelength Band - Al-Mansoori, Mohammed Hayder (2008)

(untitled)
In this dissertation, the design and development of the multiwavelength Brillouin- Erbium fiber laser (BEFL) sources operating in the L-band transmission window is presented and characterized. Four different laser designs have been successfully demonstrated using a combination of stimulated Brillouin scattering effect in optical fiber and Erbium-doped fiber (EDF) amplification. The experimental results obtained from the characterization and optimization of these laser structures are the threshold power, number of the Stokes signals generated, Stokes signals power, self-lasing oscillation and the tuning range. The results are taken from the studies which have been carried out to analyze the effects of 1480 nm pump power, Brillouin pump (BP) power, BP wavelength and single mode fiber (SMF) length. The first laser structure is an efficient multiwavelength L-band BEFL pumped by a 1480 nm pump laser in a linear cavity configuration with direct BP injection into SMF. The issue of low gain efficiency of the L-band in the EDF lasers is resolved with the efficient linear cavity structure and the 1480 nm pumping scheme. The proposed laser structure exhibits a low threshold power of 18 mW and a maximum number of 26 stable output channels with 0.089 nm (10.5 GHz) channels spacing. The second and third laser structures are focused on the enhanced multiwavelength BEFL, in which the BP power is pre-amplified before entering the SMF within the laser cavity. The BP pre-amplification techniques - single pass and double pass represent a new mode of operation of multiwavelength BEFL’s. This intra-cavity BP pre-amplification provided by the EDF has created higher intensity of Brillouin Stokes signals generated in the single-mode fiber that leads to the homogenous gain saturation. This effect is able to suppress the built-up of the self-lasing cavity modes in a wider wavelength range and the number of output channels is also enhanced as compared to the conventional BP direct injection. Output of more than 33 laser channels is achieved and the tuning range is almost doubled than that of the conventional BP direct injection technique. Finally, for the fourth laser configuration, the multiwavelength BEFL incorporates either the amplified fiber loop mirror (AFLM) or non-linear amplified fiber loop mirror filter (AFLMF). Fifty-four stable output channels, with 0.089 nm channels spacing, have been achieved. A non-linear AFLMF which induces wavelengthdependent cavity loss and serves as an amplitude equalizer is employed to shift and flatten the EDF gain spectrum. Two control mechanisms have been demonstrated to shift and flatten the EDF gain profile through the adjustment of the polarization controller in the AFLMF. Therefore, the multiwavelength BEFL could be tuned over the whole L-band window from 1570 nm to 1610 nm with the average number of 24 output channels. In addition, flattening the EDF laser oscillation overcomes the requirements of the BP wavelength tuning, in conjunction with the adjustment of the polarization controllers in the fiber loop.